Analisis Beban Kerja Guru Disertai Disiplin Serta Kompensasi Dalam Memprediksi Kinerja Mengajar - Syarifudin, M. Amir; Askafi, Eka; Rusandy, Deby Santyo (REVITALISASI : Jurnal Ilmu Manajemen, 2025)
This study aims to evaluate the impact of work discipline, workload, and compensation on teacher performance at SMKN 1 Purwoasri, Kediri, East Java. A quantitative approach was used, with 62 teachers as the sample, selected through saturated sampling. Data were collected using questionnaires and analyzed with descriptive statistics, validity and reliability tests, normality, multicollinearity, heteroscedasticity, regression analysis, coefficient of determination (R²), and hypothesis testing, using SPSS version 22 for Windows. The results indicate that work discipline does not have a significant impact on teacher performance, while workload and compensation both show a significant influence. Furthermore, the three variables collectively have a significant effect on teacher performance.